The Influence of Small Business on the Development of the Country's Economy in Modern Conditions ("Journal "U". Economy. Management. Finance.", 2023)
Currently, projects aimed at supporting small and medium-sized businesses are becoming increasingly important. Undoubtedly, this trend is due to the current severe need to search for and increase domestic resources, which in the long run would help strengthen the country's economic potential. Hence, there is a certain interest in considering the contribution of SE subjects to the development of the national economy, which was the subject of this article. The paper presents an analysis of the state of small business in Russia, an assessment of the factors affecting the activities of small enterprises in modern conditions, and also formed comprehensive conclusions.
Keywords: small business; economic development; measures to promote entrepreneurship; crisis factors